2010
DOI: 10.12693/aphyspola.117.849
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Adsorptive Properties οf Organobentonites

Abstract: In this paper partial and complete substitution of cations in the interlayer region of clay with different amounts of two aliphatic ammonium cations was performed with aim of synthesis of organobentonites with multipurpose adsorption properties. Domestic clay from Bogovina was submitted according to a common procedure used for the obtention of organobentonite, which comprises the following steps: grinding, sieving, Na-exchange, cation exchange and drying. The samples were characterized by X-ray diffraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is interesting to note that the modified samples, i.e., BCH, LCH, or LCAH possess two distinct vibration bands at 2925 and 2850 cm −1 that are associated with the asymmetric and symmetric C-H stretching vibrations of the -CH2 group, respectively. A band at 1480 cm −1 is assigned to the bending mode of the CH2 group [26,29,30]. This confirms the introduction of the HDTMA molecule within the clay network of all these modified solids.…”
Section: Characterization Of Hybrid Materialsmentioning
confidence: 69%
“…It is interesting to note that the modified samples, i.e., BCH, LCH, or LCAH possess two distinct vibration bands at 2925 and 2850 cm −1 that are associated with the asymmetric and symmetric C-H stretching vibrations of the -CH2 group, respectively. A band at 1480 cm −1 is assigned to the bending mode of the CH2 group [26,29,30]. This confirms the introduction of the HDTMA molecule within the clay network of all these modified solids.…”
Section: Characterization Of Hybrid Materialsmentioning
confidence: 69%
“…1 The previous studies of this group have shown that the incorporation of QAC in the different amounts corresponding to the cation exchange capacity (CEC) of smectite leads to the formation of different molecular arrangements, depending on the structure and QAC alkyl chain length. 16,[25][26][27] Short-chain QAC dominantly forms monolayers with characteristic d 001 ≈ 1.4 nm, while longer chain QAC make bilayers structure (d 001 ≈ 1.8 nm) with the alkyl chain axes parallel to the silicate layers. 1 Pseudo-trimolecular arrangement structures of kinked alkyl chains are observed with highly charged smectites and/or long surfactant cations and exhibit d 001 ≈ 2.2 nm.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Compared to polyaniline, as surface modifiers, CTAB seems to be favored. CTAB molecule for surface modification to create positive charge has been incorporated into zeolite [24], bentonite type clay [25], and silica [17][18][19][20][21][22][23]. The most silica modified with CTAB [17][18][19][20][21][22][23] was prepared from commercial material of tetra ethyl ortho silane (TEOS).…”
Section: Introductionmentioning
confidence: 99%